Quality Management Adoption in Building Materials Firms Improves Productivity and Profitability: Penerapan Manajemen Kualitas di Perusahaan Bahan Bangunan Meningkatkan Produktivitas dan Keuntungan - Ugli, Hakberdiev Ulugbek Nasrullo (Academia Open, 2025)
General Background: The building materials industry plays a critical role in national economic growth, particularly in developing countries where infrastructure demands are rising. Specific Background: Despite increased output, quality assurance remains underdeveloped in many enterprises, limiting both competitiveness and sustainability. Knowledge Gap: Although global quality management systems such as ISO 9001, TQM, and Six Sigma are well-studied, their effective adaptation to local contexts like Uzbekistan remains insufficiently explored. Aims: This study investigates the practical application of quality management principles in Uzbekistan’s building materials sector, comparing enterprises with and without ISO 9001 implementation. Results: The findings reveal that ISO-certified companies experience significantly higher customer satisfaction (85% vs. 60%), lower defect rates (3% vs. 12%), and increased production efficiency (92% vs. 75%). Employee training also correlates with reduced turnover and operational stability. Novelty: The study combines empirical analysis with national and international theoretical frameworks to propose locally adaptable strategies, bridging the gap between global standards and regional realities. Implications: Strategic investment in human capital and quality processes enhances productivity and profitability, confirming that quality management is not merely a technical function but a core strategic asset for sustainable industrial development. Highlights: Strategic Importance: Implementing ISO 9001 boosts customer satisfaction (↑85%) and reduces defects (↓3%) a core metric for global competitiveness. Human Capital: Enterprises investing in staff training show lower turnover and fewer production stops, proving workforce quality directly impacts product quality. Economic Benefit: Spending on quality isn’t a cost, it’s an investment; higher quality spend leads to higher profits and significantly less product loss. Keywords: Quality Management, Building Materials, ISO 9001, TQM, Production Efficiency